Cancer mortality in England in relation to levels of naturally occurring fluoride in water supplies. Issue 1 (March 1985) - Chilvers, C; Conway, D
Abstract : Sixty-seven small areas in England have been classified into four groups according to the level of naturally occurring fluoride in their water supplies. Small area mortality statistics for 1969-73 have been used to look for differences in cancer mortality in relation to fluoride levels. Deaths from all cancers and from cancer at 12 specific body sites have been examined; no consistent trends in mortality are apparent. These results provide no evidence of a harmful effect of naturally occurring fluoride in water supplies.